The Role of Organizational Culture Factors to Psychological Contracts (Transactional Contracts, Balance Contracts, and Relational Contracts) - DWIYANTI, Retno; SUWARTI, SUWARTI; NAIMAH, Tri (Journal of Advanced Research in Law and Economics, 2019)
The exchange of relationships between employees and firms is influenced by the beliefs and values that hold the human resources in carrying out its obligations and its behavior within the organization. This study aims to determine how big the relationship and the role of organizational culture to psychological contracts. Data were collected using two scales, namely organizational culture scale, and psychological contract scale. The results showed that there was a very significant relationship between organizational culture and psychological contracts, with an effective contribution of 5.047 percent. Based on the analysis of the relationship between organizational culture factors with psychological contracts can be shown the result that the organizational identity factor has a positive and very significant relationship with the psychological contract, with an effective contribution of 10.609 percent. The results also show that the organizational identity factor has a positive and very significant relationship with the transactional psychological contract. The organizational identity factor has a positive and significant relationship with the balance psychological contract. Collective commitment factor and Stability of social system have a positive and very significant relationship with balance psychological contract. Collective commitment factors have a positive and highly significant relationship with the relational psychological contract.